PENGGUNAAN ALAT PERAGA MISTAR BILANGAN BULAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN 8 LABUAN PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Lisman Lisman; Wahyuni H Mailili (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The purpose of this study is to describe the use of the integer crossbar in improving the learning outcomes of Grade VI students of SDN 8 Labuan on the addition and subtraction of integers. This type of research refers to classroom action research (CAR) with a qualitative approach. The design of this study uses the Kemmis and Mc.Taggart model which consists of: 1) planning 2) implementing actions 3) observation and 4) reflection. Data collection techniques used were the provision of tests, interviews, observations and field notes. The instrument used was a test in the form of description. Data collection is done through three stages: (1) reducing data, (2) presenting data, and (3) drawing conclusions.The results showed that the student activities and teacher activities in learning activities in the first cycle reached the Good category and the second cycle was very good. The results of the analysis of the end of the first cycle test results obtained the percentage of the average value with the absorption of students reached 74.11% and classical learning completeness reached a percentage of 77.78% of 18 students. While the final test analysis cycle IIincreased according to the results of observations of student and teacher activities, the average percentage of students' absorption rate reached 80.22% with classical learning completeness reaching the target percentage of 100% from 18 students. This has shown there is an increase in the learning outcomes of students of class VI SDN 8 Labuan on the material addition and subtraction of integers by the use of crossbar numbers